Biological and Immunological Effects of Penicillic Acid on Mice liver and Intestine - Qasim, Suhaib Raad; Alsamarrae, Khluood W; Abdul-Ratha, H. A.; Sattar, Linda F. Abdul (International Journal of Aquatic Research and Environmental Studies, 2026)
cThe aim of the present study was to investigates the effect of penicillic acid on some morphological and biochemical changes induced in mice as a result of penicillic acid mycotoxicosis. The results showed that the intraperitonal injection of penicllic acid to mice caused pathological signs of marked increase in body weight, dyspnea, shivering, bristling up of hair, hair falling, anomalies of eyes and irritation around neck. A biochemical study on liver function was conducted by measuring GOT and GPT enzyme levels. The results indicated an increase in GOT and GPT enzyme levels in treated mice compared with control mice which indicating failure in liver function. A radial immunodiffusion plate kit was used to assay immunoglobulin IgG, IgM, and IgA levels, results report an increase of these immunoglobulin level in treated mice which indicating immune response to this toxin.in addation ,treatment of mice with penicillic acid showed an increase in total and differential count of leukocyte.